Resorbable Purified Porcine Skin Gelatin Cross-Linked with Glutaraldehyde Spheres for Preoperative Embolization of Carotid Body Paraganglioma - Hohenstatt, Sophia; Angileri, Salvatore Alessio; Granata, Giuseppe; Paolucci, Aldo; Ierardi, Anna Maria; Carrafiello, Gianpaolo; Curci, Ruggiero (Acta Biomedica Atenei Parmensis, 2021)
Chemodectomas are rare neuroendocrine tumors that typically arise at the carotid bifurcation and progressively englobe the internal and external carotid artery. Surgical asportation of the capsulated mass is the elective treatment. Pre-procedural embolization of this high vascular tumors is highly recommended because it has shown to improve surgical outcome by reducing both, mean blood loss and total operation time. Many different embolization techniques have been described in literature. In the here presented case we opted for an endovascular approach using resorbable purified porcine skin gelatin cross-linked with glutaraldehyde microspheres (Optisphere - MEDTRONIC) as an embolic agent. These turned out to be very safe and effective in improving surgical outcome by reducing operative blood loss and thus reducing treatment-related morbidity.